2006
DOI: 10.1038/sj.onc.1209996
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 and p53/47 are controlled by alternative mechanisms of messenger RNA translation initiation

Abstract: P53 controls the growth and survival of cells by acting in response to a multitude of cellular stresses. It is, however, not yet fully understood how different p53 activation pathways result in either cell cycle arrest or apoptosis. We and others have described an N-terminally truncated p53 protein (p53/47) originating from a second translation initiation site in the p53 messenger RNA (mRNA), which can interact with p53 and impose altered stability and transactivation properties to p53 complexes. Here we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
138
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 42 publications
11
138
0
Order By: Relevance
“…p53 isoforms gain functions V Olivares-Illana and R Fåhraeus the p53 response (Candeias et al, 2006). Further work showed that suppression of PERK activity, through overexpression of either a dominant-negative PERK or small interfering RNA, resulted in the suppression of p53/47 expression, indicating that PERK is the signal transducer between the ER and p53/47 expression ( Figure 2) (Bourougaa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…p53 isoforms gain functions V Olivares-Illana and R Fåhraeus the p53 response (Candeias et al, 2006). Further work showed that suppression of PERK activity, through overexpression of either a dominant-negative PERK or small interfering RNA, resulted in the suppression of p53/47 expression, indicating that PERK is the signal transducer between the ER and p53/47 expression ( Figure 2) (Bourougaa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, p53/47 was discovered due to the fact Mdm2 can promote the initiation of translation of both p53 and p53/47, but only targets the former for degradation (Yin et al, 2002). Later work showed that translation initiation of p53 and p53/47 can be controlled by separate and, to some extent, competing mechanisms of translation, so that suppression of capdependent translation of p53 results in an increase in the synthesis of p53/47 (Candeias et al, 2006). Insertion of an open-reading frame followed by a hairpin structure in the 5 0 -untranslated region of p53 resulted in an increase in p53/47 synthesis and a decrease in p53, indicating that cap-independent mechanisms of initiation control p53/47 translation via an internal ribosome entry site (IRES) structure located in the region of þ 1 to þ 120 of p53.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA of human Mdm2 was kindly provided by N. Varin-Blank (Institut Cochin), and the p53 plasmid was described previously (34). Various tagged forms of ␤-arr2 have been described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Several isoforms of p53 have been identified (Courtois et al, 2002;Candeias et al, 2006;Grover et al, 2009;Marcel and Hainaut, 2009), and point mutations influencing the functionality of p53 were elucidated and mimicked in vivo (de Vries et al, 2002;Wijnhoven et al, 2005;Hoogervorst et al, 2005a;Iwakuma and Lozano, 2007;Heinlein et al, 2008). The p53 gene is the most frequently mutated gene in cancer and analysis of many different human tumor types have shown a high prevalence of missense mutations located primarily in the central DNA-binding domain (Levine, 1997).…”
Section: Introductionmentioning
confidence: 99%